PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN CAT PROPAN PADA TOKO TIRTA BANGUNAN SENTUL - Muhamad Alpian; Aris Arianto (Journal of Research and Publication Innovation, 2025)
The purpose of this study is to ascertain how pricing and product quality affect consumers' decisions to buy propane paint products. The participants in this study were Toko Tirta Bangunan Sentul customers. This study employs a quantitative approach. Primary and secondary data collecting are the methods employed. Probability sampling is the auxiliary method employed. There are 7,866 individuals in the population, and 90 samples were taken. Validity, reliability, normality, multicollinearity, autocorrelation, heteroscedasticity, simple linear regression, multiple linear regression, simple correlation coefficient, multiple correlation coefficient, coefficient of determination analysis, t test, and f test are the data analysis methods that are employed. The tcount value of 8.071> table 1.985 and a significant level of 0.000 <0.05 indicate that the product quality variable (X1) has a positive and substantial impact on purchase decisions (Y), according to the t test results. With a correlation coefficient of 0.652 and a strong association level, the product quality variable (X1) influences purchases (Y) by 42.5%. The tcount value of 10.383> t table 1.985 and a significant level of 0.000 <0.05 indicate that the price variable (X2) has a positive and substantial impact on purchase decisions (Y), according to the t test results. Purchasing decisions (Y) are influenced by the price variable (X2) by 55.1%, with a significant correlation coefficient of 0.742. The Fcount value of 73.594> Ftabel 3.09 and a significance of 0.000<0.05 demonstrate that the factors of product quality (X1) and price (X2) concurrently have a positive and substantial impact on purchase decisions (Y), according to the results of the f test. With a correlation value of 0.793 and a strong association level, the variables of price (X2) and product quality (X1) have a 62.9% impact on decisions to buy (Y).